2008
DOI: 10.1523/jneurosci.0257-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Aquaporin-4-Deficient Mice Have Increased Extracellular Space without Tortuosity Change

Abstract: Aquaporin-4 (AQP4) isϪ/Ϫ mice, and no differences in and k between the two genotypes. This is the first direct comparison of ECS properties in adult mice lacking AQP4 water channels with wild-type animals and demonstrates a significant enlargement of the volume fraction but no difference in hindrance to TMA ϩ diffusion, expressed as tortuosity. These findings provide direct evidence for involvement of AQP4 in modulation of the ECS volume fraction and provide a basis for future modeling of water and ion transpo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
113
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(132 citation statements)
references
References 30 publications
15
113
1
Order By: Relevance
“…In accord with our finding of increased seizure susceptibility and reduced ECS volume in Has3 Ϫ/Ϫ mice, decreased seizure susceptibility and enlarged ECS volume were previously reported in aquaporin-4-deficient mice (Binder et al, 2004;Yao et al, 2008). We also note that other studies have demonstrated modulation of ongoing epileptiform activity by osmotically induced ECS volume changes (Andrew et al, 1989;Traynelis and Dingledine, 1989;Dudek et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…In accord with our finding of increased seizure susceptibility and reduced ECS volume in Has3 Ϫ/Ϫ mice, decreased seizure susceptibility and enlarged ECS volume were previously reported in aquaporin-4-deficient mice (Binder et al, 2004;Yao et al, 2008). We also note that other studies have demonstrated modulation of ongoing epileptiform activity by osmotically induced ECS volume changes (Andrew et al, 1989;Traynelis and Dingledine, 1989;Dudek et al, 1998).…”
Section: Discussionsupporting
confidence: 92%
“…Thus, the increased brain water content must reflect excess water in brain parenchyma rather than any difference in ventricular volume. If glial-conditional Aqp4 −/− animals show an increase in baseline extracellular space volume similar to that reported for constitutive Aqp4 −/− (22,23), this would explain the excess water content.…”
Section: Discussionmentioning
confidence: 54%
“…Aquaporins clearly do play diverse roles in brain water balance in health and disease [9,84] and such concepts have undoubtedly informed the 'glymphatic' hypothesis. The previous studies performed on AQP4-deficient mice have demonstrated that such animals exhibit an increased brain ECS volume fraction [196], increased basal brain water content [73], and larger intracranial pressure elevations in response to induced vasogenic (non-cellular) oedema [134], suggesting that AQP4 indeed plays critical roles in the transport of water between brain compartments as well as the formation and resolution of oedema. The key question for the 'glymphatic' concept is just what role astrocytic AQP4 may play in the circulation of fluid in perivascular compartments and how its deletion affects such circulation.…”
Section: Blood Vessels and The Perivascular Spacementioning
confidence: 99%